The effect of paleolithic diet on glucose metabolism and lipid profile among patients with metabolic disorders: a systematic review and meta-analysis of randomized controlled trials. Issue 17 (25th September 2022) - Sohouli, Mohammad Hassan; Fatahi, Somaye; Lari, Abolfazl; Lotfi, Mojtaba; Seifishahpar, Maryam; Găman, Mihnea-Alexandru; Rahideh, Seyedeh Tayebeh; AlBatati, Saud K.; AlHossan, Abdullah M.; Alkhalifa, Sara A.; Alomar, Sara A.; Abu-Zaid, Ahmed
Abstract: Objective: Several randomized clinical trials (RCTs) have investigated the effects of the Paleolithic diet (PD) in adult patients suffering from metabolic disorders. However, the results of these RCTs are conflicting. Therefore, we conducted a systematic review and meta-analysis to assess the effects of the PD in patients with metabolic disorders. Methods: We searched the PubMed/Medline, Scopus, Cochrane Databases, Google Scholar, Web of Science, and Embase databases up to June, 2020. The data were pooled using a random-effects model. From the eligible publications, 10 articles were selected for inclusion in this systematic review and meta-analysis. The meta-analysis was performed using a random-effects model. The heterogeneity was determined using the I 2 statistics and the Cochrane Q test. Results: The pooled results from the random-effects model showed a significant reduction of the homeostatic model assessment of insulin resistance (HOMA-IR) (weighted mean difference, WMD: −0.39, 95% CI: −0.70, −0.08), fasting insulin (WMD: −12.17 μU/mL, 95% CI: −24.26, −0.08), total cholesterol (WMD: −0.32 mmol/l, 95% CI: −0.49, −0.15), triglycerides (WMD: −0.29 mmol/L, 95% CI: −0.42, −0.16), low-density lipoprotein cholesterol (WMD: −0.35 mmol/L, 95% CI: −0.67, −0.03), blood pressure (BP)(WMD − 5.89 mmHg; 95% CI − 9.973 to − 1.86 for the systolic BP and WMD − 4.01 mmHg; 95% CI − 6.21 to − 1.80 for the diastolic BP values) and C-reactive protein (CRP) levels (WMD: −0.84, mg/L, 95% CI: −1.62, −0.06) in the PD group versus control group. Conclusions: Our findings provide better insights into the effect of the PD on the modulation of the glucose and lipid metabolism factors in patients with metabolic disorders, providing comprehensive information for the development of future RCTs with a high quality design.